Efektivitas Penggunaan Papan Bintang sebagai Strategi Motivasi Pembelajaran Pada Siswa Kelas 1 (Studi Kasus Di Min 1 Langsa) - fasihah Lubis; M. Witra Kusuma Kusuma; Zaifaturridha; Ahmad Fuadi Fuadi (LP2M STAI Darul Kamal NW Kembang Kerang, 2026)
This study aims to describe the effectiveness of using a star board as a motivational learning strategy for first-grade students at MIN 1 Langsa. The background of the study is based on the low levels of student motivation, discipline, and engagement in learning, indicating the need for strategies that align with the characteristics of lower-grade students. This research employed a qualitative approach with a single case study design. Data were collected through observations, interviews with the homeroom teacher, principal, and students, as well as documentation of students’ behavioral development and academic achievements. Data analysis was conducted through the processes of data reduction, data display, and conclusion drawing. The findings reveal that the implementation of the star board provides positive reinforcement that significantly enhances students’ learning motivation. Students became more disciplined, focused, active in asking questions, and enthusiastic in completing tasks. Observations and interview results indicate consistent positive behavioral changes from week to week, reflected in the increasing number of stars earned and a more conducive classroom atmosphere. This strategy also fostered responsibility, cooperation, and sportsmanship among students. The star board proved effective as a visual medium and reinforcement strategy in improving motivation and learning behavior among lower-grade students.